(untitled) - Dunlap, Richard A. (Australia, 2019)
The text emphasizes the complexity of energy issues and the need for a multidisciplinary approach to solve today's energy problems. Quantitative end-of-chapter problems require students to analyze information, use material from previous chapters, correlate data from various sources, and interpret graphical data and interpolate values. Students see real problems encountered in producing and using energy and realize that while exact calculations are important, a broad-based analysis is often most appropriate.
Keywords: Năng lượng tái sinh,Tòa nhà bền vững,Renewable energy sources,Sustainable buildings